Genetic markers of vascular aging. (October 2007) - Khaleghi, Mahyar; Kullo, Iftikhar J
Age is a powerful determinant of cardiovascular risk, being associated with a number of deleterious changes in the cardiovascular system. Increased arterial stiffness is an almost ubiquitous accompaniment of aging. However, there is significant variability in age-related arterial changes between individuals likely due, in part, to genetic factors. Measures of arterial stiffness such as pulse pressure and aortic pulse wave velocity have been shown to be heritable, indicating that genetic factors play a role in the interindividual variation of these phenotypes. Linkage analyses in related individuals have identified several genomic regions that may influence measures of arterial stiffness, and numerous association studies have investigated whether polymorphisms in candidate genes are related to this phenotype. Genome-wide association studies using 500, 000 single nucleotide polymorphisms or more are now feasible and will accelerate the discovery of specific genetic polymorphisms that influence vascular aging/stiffness. Such findings will facilitate the development of novel therapies to retard vascular aging.